Computer-Animation on NCE Students’ Academic Performance in Vertebrate Anatomy and Physiology in Colleges of Education - N. A. Ala; A. M. Ishyaku; S. B. Adamu; A. O. Onojah (Universitas Pendidikan Ganesha, 2022)
The low ability of students causes students to have difficulty understanding some Biology concepts. In addition, the time given for biology practicum is still limited. The purpose of this study was to analyze the differences in biology students' performance when taught VAP using animation packages and lecture methods. This study adopts a quasi-experimental design. The population in this study was 60 Biology students. The method used to collect data is observation, questionnaires, and tests. The instruments used in collecting data were questionnaires and question sheets. The technique used to analyze the information is inferential statistical analysis. The study results showed a significant difference between the performance of Biology students when taught VAP using the animation package and the lecture method supporting the experimental group. Thus, this research concludes that the animation strategy improves Biology students' performance in VAP. The implication is that learning strategies play a positive role in the teaching and learning of Biology in higher education institutions. The study recommends that higher education Biology lecturers be encouraged to incorporate animation packages into Biology teaching.